NIH policies on experimental studies with humans. (February 2018) - Riley, William; Riddle, Melissa; Lauer, Michael
The recently updated US National Institutes of Health clinical trials policies will apply broadly to studies involving experimental manipulations of humans. These studies will require registration and reporting in ClinicalTrials.gov, grant application submission under a clinical trials funding opportunity announcement, and Good Clinical Practice training for investigators.